ØªØ£Ø«ÙŠØ± ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ø¥Ø¹Ù„Ø§Ù… Ø§Ù„Ø³ÙŠÙ†Ù…Ø§Ø¦ÙŠØ© Ø¹Ù„Ù‰ Ø²ÙŠØ§Ø¯Ø© ØÙØ¸ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª - Nur Maya; Fitria Mandasyahri (Institut Agama Islam Darusssalam Blokagung, 2021)
The objectives to be achieved in this study are: 1) To determine the effect of film media on learning Arabic at madrasah aliyah al-amiriyah. 2) To determine the increase in memorizing mufrodat of class X IPA 4 students at madrasah aliyah al-amiriyah. 3) To determine the effect of film media on the increase in memorizing mufrodat of class X IPA 4 students at madrasah aliyah al-amiriyah. In this study, after testing the hypothesis, the following results were obtained: 1) Application of film media in Arabic lessons for class X IPA 4 students at madrasah aliyah al-amiriyyah with an average questionnaire result of 63.48 in the good category. 2) Memorization of Arabic mufrodat class X IPA 4 students of madrasah aliyah al-amiriyyah with an average of 67.58 which is in the 63-68 interval with a fairly good category. 3) r_count is greater than rtable, both at the significant level of 5% or 1%, which means that Ho is rejected and Ha is accepted, so there is a significant influence between the film media on the increase in memorizing the mufrodat of class X ipa 4 students of madrasah aliyah al-amiriyyah in the academic year 2018-2019. With the value of the influence of variable X on variable Y of 38.44%, it means that variable X has an effect on variable Y by 38.44% and there are still 61.56% other things that affect variable Y.